Original papersLipomatosis - Iljin, Aleksandra; Kruk-Jeromin, Julia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Introduction: Lipomatosis is the excessive accumulation of subcutaneous adipose tissue mostly on the extremities, trunk and buttocks, and sometimes it coexists with systemic lipomas. Aetiopathogenetic theories include defect of brown adipose tissue, alterations in lipid metabolism, and hereditary factors, but alcoholism, neuropathies, and metabolic disorders have also been also underlined. Treatments of choice are excisional surgery, liposuction, and lipectomy, or lipolysis sometimes together with a reducing diet, and pharmacological therapy. Material and methods: There were 6 patients who underwent surgical treatment for multiple lipomas at the Department of Plastic Surgery, Medical University of Łódź in the years 1999-2008. We analysed aetiopathogenesis of the lipomatosis, coexistence of other anomalies, and methods of surgical management of the tumours. Results: Postoperative results in patients of the studied group were good. Conclusions: We confirmed neither the influence of aetiopathogenetic factors nor the coexistence of similar systemic disorders.